(untitled) (Journal of the College of Basic Education, 2022)
Researchers in Iraq often use intelligence tests to measure the intelligence of middle school students for research or diagnostic purposes, and it seems that they differ in choosing the intelligence used in these studies in terms of the theoretical frameworks behind these tests. In its theoretical framework, there are three capabilities (analytical, practical, and creative), and most of the tests that were relied upon or that were adopted neglected the factorial structure of it. Reaching the extent of congruence between the factorial structure of the test according to a theoretical framework